PROFIL PENYIMPANAN OBAT DI GUDANG INSTALASI FARMASI RUMAH SAKIT MITRA MANAKARRA MAMUJU SULAWESI BARAT - Hokilia, Resky Nov; Herman, Hendra; hasrawati, A. (PHARMACY UMI JOURNAL SYSTEM, 2024)
Pharmaceutical services in hospitals including the management of pharmaceutical supplies including drug storage to pay attention to storage so that errors do not occur during the drug storage process and drug storage is a very important step in maintaining the quality of medicines. Drug storage must guarantee the quality and safety of the drug in accordance with pharmaceutical requirements. The purpose of this study was to determine the profile of drug storage in the Pharmacy Installation Warehouse at Mitra Manakarra Mamuju Hospital, West Sulawesi and its compliance with regulations in force in Indonesia. This study used a descriptive method by conducting interviews and observations. The respondents in this study consisted of the person in charge of the pharmacy and the person in charge of the warehouse at the Pharmacy Installation at Mitra Manakarra Hospital Mamuju, West Sulawesi. Collecting data in research by means of observation, interviews and data analysis. Analysis Percentage of storage areas in good condition with a yield value of 93.1%, storage areas for narcotics, psychotropics and precursors in good condition with a yield value of 100%, method and system aspects in good condition with a yield value of 91.6% and stock cards in good condition with yield values 90%.